2021
DOI: 10.1111/sltb.12822
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for suicide attempts among U.S. military veterans: A 7‐year population‐based, longitudinal cohort study

Abstract: Background: Population-based data on risk factors for suicide attempts among veterans remains limited. Methods:A national probability sample of 2307 veterans was followed over the course of four timepoints spanning seven years to examine how a range of baseline risk factors predict incident suicide attempt. Suicide attempt data were aggregated into a single follow-up timepoint.Results: Sixty-two veterans (3.1%) reported attempting suicide during the 7-year period. The strongest risk factors for suicide attempt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…While it has been recommended that Veterans with MH diagnoses, physical health comorbidities, and housing concerns remain engaged in care, research shows that there are many other factors associated with suicide risk 23 . Nichter and colleagues 23 recently led a longitudinal cohort study among Veterans and found that loneliness, frequent thoughts of self‐harm, exposure to traumatic events, and lower dispositional gratitude are all strong risk factors for future suicide attempts. Anger and lack of social support have also been shown to play a role in suicide risk among Veterans 24 .…”
Section: Discussionmentioning
confidence: 99%
“…While it has been recommended that Veterans with MH diagnoses, physical health comorbidities, and housing concerns remain engaged in care, research shows that there are many other factors associated with suicide risk 23 . Nichter and colleagues 23 recently led a longitudinal cohort study among Veterans and found that loneliness, frequent thoughts of self‐harm, exposure to traumatic events, and lower dispositional gratitude are all strong risk factors for future suicide attempts. Anger and lack of social support have also been shown to play a role in suicide risk among Veterans 24 .…”
Section: Discussionmentioning
confidence: 99%
“…whole-genome sequencing studies) in combination with other environmental factors (e.g. trauma history; Nichter et al, 2022) may potentially help inform risk stratification and clinical decision-making for suicidality in the future. Indeed, as highlighted in a recent review (Murray et al, 2021), genomic data needed to calculate PRS are inexpensive and easy to collect, and could help inform clinical decision-making in a similar way that clinicians currently use information recorded about family history of psychopathology to stratify patients at most risk and in need of a greater level of surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47] Investigations into the disturbing prevalence suicide among U.S. military and veterans confirmed this connection. [48][49][50] Loneliness is found to be twice the contributor to premature death and cardiovascular illness as obesity and four times that of environmental factors, due to complex neurophysiological consequences (e.g., altered inflammatory and immune responses, and elevated cholesterol, heart rate, vascular resistance, and blood pressure) and an adverse impact on self-care or social support. 33,35,51,52 Following a review of two decades of human and animal research, the authors of the Evolutionary Theory of Loneliness posit eight neurophysiological pathways between loneliness and medical illness that include poor sleep quality, heightened activation of the HPA axis, selectively activated sympathetic tonus, altered transcriptome dynamics, decreased viral immunity, increased inflammatory response, increased prepotent responding, and depressive J o u r n a l P r e -p r o o f symptomatology.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%